2003
DOI: 10.1038/sj.onc.1206339
|View full text |Cite
|
Sign up to set email alerts
|

SKP2 associates with p130 and accelerates p130 ubiquitylation and degradation in human cells

Abstract: p130 is a member of the retinoblastoma family of pocket proteins, which includes pRB and p107. Unlike pRB and p107, p130 protein levels decrease dramatically following its hyperphosphorylation starting in the mid-G1 phase of the cell cycle. However, the mechanism leading to p130 downregulation is unknown. We have found that the proteasome inhibitor, lactacystin, inhibited p130 downregulation in T98G cells progressing through the G1/S transition and S phase and that p130 is multiubiquitylated in 293 cells. We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 39 publications
4
80
0
1
Order By: Relevance
“…6A, p107 and RB levels were markedly diminished after CDK4 inhibition, whereas endogenous p130 levels were significantly increased. These data are consistent with the divergent regulation of the RB family during cell cycle progression in staged cells (28,29) and with experiments testing the effect of PD0332991 in asynchronously dividing hepatocellular carcinoma cells (30). Moreover, levels of p107 and p130 were significantly increased during a short duration (6 h) of MG132 treatment, whereas RB levels were modestly diminished.…”
Section: Regulation Of Rb P107 and P130 Localization And Stability supporting
confidence: 75%
See 3 more Smart Citations
“…6A, p107 and RB levels were markedly diminished after CDK4 inhibition, whereas endogenous p130 levels were significantly increased. These data are consistent with the divergent regulation of the RB family during cell cycle progression in staged cells (28,29) and with experiments testing the effect of PD0332991 in asynchronously dividing hepatocellular carcinoma cells (30). Moreover, levels of p107 and p130 were significantly increased during a short duration (6 h) of MG132 treatment, whereas RB levels were modestly diminished.…”
Section: Regulation Of Rb P107 and P130 Localization And Stability supporting
confidence: 75%
“…For example, RB and p107 are active in cycling cells, whereas p130 functions predominately in quiescent cells that have exited from the cell cycle. Experiments performed with staged cells showed that steady state p130 levels peak in G 0 , in contrast to RB and p107, which increase as cells progress through G 1 (28,29). Consistently, CDK4 activity has opposite effects on p107 and p130 steady state levels; inhibition of the enzyme leads to diminished levels of p107 and higher levels of p130 (30).…”
Section: /P53mentioning
confidence: 99%
See 2 more Smart Citations
“…The most important substrates for SKP2 include p27 kip1 cyclin-dependent kinase inhibitor and cyclin E, both of which interact with cyclindependent kinase 2 to regulate G 1 -S transition (7). SKP2 has also been implicated in regulating the proteosome-mediated degradation of c-myc, p21 cip1 , p57 kip2 , and p130-Rb2 (8)(9)(10)(11)(12)(13). Elevated SKP2 expression has been shown in breast, colorectum, lung, and stomach carcinomas and lymphomas (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%